Fatty Acid Composition in Feeds and Plasma of Canadian Premature Infants. Issue 1 (July 2016) - Hossain, Zakir; MacKay, Dylan; Friel, James K.
ABSTRACT: Objectives: The objective of the present exploratory study was to investigate how the fatty acid (FA) composition of different food sources for preterm infants including breast milk (BM), formula (F), human milk fortifiers (HMFs), and total parenteral nutrition (TPN) impacted preterm infant's plasma FA. The associations between FA content of plasma with antioxidant enzyme activity and cognition were also evaluated. Methods: Thirty-two premature infants were included in the present study. Five different feeds (BM, F, BM + F, BM + HMF, and TPN) were provided. Foods and preterm infant plasma samples were collected at the same time on the same day biweekly where possible. Separation and identification of the plasma and food FA methyl esters were performed by gas-liquid chromatography. Antioxidant enzymes were measured. The Bayley Scale of Infant Development version III was used to evaluate cognition. Results: In food sources, BM contained significantly lower stearic acid (C18:0) ( P < 0.05), oleic acid (C18:1n9) ( P < 0.01), linoleic acid (C18:2n6) ( P < 0.01), α-linoleic acid (C18:3n3) ( P < 0.01), and arachidonic acid (C20:4n6) ( P < 0.05) compared with the F. Palmitic acid (C16:0) was significantly higher ( P < 0.05) in the BM + HMF compared with the BM. Stearic acid (C18:0) was significantly higher ( P < 0.05) in the BM + F and BM + HMF compared with the BM. In the plasma lauric acid (C12:0) ( P < 0.05) and myristic acid (C14:0) ( P < 0.001) were higher in the BM-fed babies compared with the F-fed or TPN-recipient groups. Antioxidant enzymes, activities and cognition scores did not differ by feeding groups, however the study may not have been powered to detect these differences. Conclusions: The type, and therefore quality, of fatty acids is an important consideration when selecting what is fed to premature infants because differences in feed fatty acids were seen in some plasma fatty acids in the study.